2023
DOI: 10.1002/smi.3299
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth and health‐related quality of life in cancer survivors: Does fatigue moderate the link?

Maria‐Chidi C. Onyedibe,
Patricia Blickle,
Martina E. Schmidt
et al.

Abstract: Interest in post‐traumatic growth (PTG) as a predictor of health‐related quality of life (HRQoL) is currently gaining attention. However, current evidence is still inconclusive on the nature of this relationship. The first objective of this study was to investigate the relationship between PTG and global HRQoL among cancer survivors. We further investigated the moderating role of fatigue in the association between PTG and global HRQoL. In the FiX study (Fatigue in Germany ‐ Examination of prevalence, severity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Previous studies have indicated that increasing the level of post-traumatic growth in patients can improve their psychological well-being, thereby aiding them in their fight against the disease and promoting their overall physical and mental health. 13 Social support is pivotal in enabling individuals to face their illness positively, effectively reducing psychological distress, and enhancing the QOL. 14 Notably, strong social support has demonstrated efficacy in reducing the anxiety experienced by gynecological oncology patients, aiding their recovery from disease, and improving their QOL.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that increasing the level of post-traumatic growth in patients can improve their psychological well-being, thereby aiding them in their fight against the disease and promoting their overall physical and mental health. 13 Social support is pivotal in enabling individuals to face their illness positively, effectively reducing psychological distress, and enhancing the QOL. 14 Notably, strong social support has demonstrated efficacy in reducing the anxiety experienced by gynecological oncology patients, aiding their recovery from disease, and improving their QOL.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of cancer research, studies have shown that PTG can promote the proliferation of white blood cells and lymphocytes and have a positive impact on the body’s immune function ( McGregor et al, 2004 ; Dunigan et al, 2007 ). In addition, PTG can alleviate patients’ psychological distress, enhance well-being, and improve the quality of life in a disease-bearing state ( Husson et al, 2017 ; Onyedibe et al, 2023 ). Given its potential benefits, a number of psychosocial interventions have emerged to promote PTG.…”
Section: Introductionmentioning
confidence: 99%